Oral Zinc supplementation in the treatment of sepsis in Nepalese children: A double-blind randomised placebo-controlled trial - Prasad Kafle, Shyam; Rauniyar, Lalan Prasad; Ahmad, Eqtedar; Koirala, Namu; Rouniyar, Maya (Journal of Kathmandu Medical College, 2021)
Background: Sepsis is one of the most common causes of morbidity and mortality in young children. Zinc supplementation has a preventive effect against diarrhoeal diseases and respiratory infections, but little is known about its effect on the treatment of sepsis. Objectives: To evaluate the benefit of oral Zinc supplementation along with standard antimicrobial therapy in childhood sepsis. Methods: A randomised, double-blind controlled trial was conducted on 164 septic children between 1-15 years of age from 15th April 2017 to 14th April 2018 in a eastern Nepal tertiary care centre. Block randomisation was done with four participants in each block. There were 21 and 20 blocks in the intervention and in the placebo group respectively. Each child received oral zinc (20 mg elemental zinc/day) or a placebo once a day for 14 days. Percentage was calculated for descriptive statistics and Chi-square for inferential statistics with 95% CI and p <0.05 for data analysis using SPSS v.16. Results: Of the participants, 84 (51.21%) received Zinc and 80 (48.79%) received a placebo in adjunct to the standard antimicrobial therapy. Most of the children 76 (46.34%) were under five years and were male 98 (59.75%), and 69 (42.07%) were underweight. Those receiving zinc and placebo had similar improvements at discharge; there was no reduction in the need for higher-order antibiotics or in the length of PICU/ hospital stay. Zinc supplementation in childhood sepsis had no benefit on decreasing mortality or decreasing severity (p >0.05). Conclusion: Zinc supplementation during childhood sepsis does not help in short-term clinical recovery.